Snow variability effect upon avalanching - P. A. Chernous; Yu. G. Seliverstov; V. E. Suchkov (Лëд и снег, 2015)
Thickness, density, shearing strength, and temperature of snow on mountain slopes are considered as stochastic fields or processes. Parameters of these fields (processes) were estimated in several geographical regions. Errors of snow stability estimation are shown to be depending on the above parameters, quantity of point measurements, and the measurement technique. Errors of different methods of space and time interpretation of measurements of the snow characteristics are discussed. Results of these studies performed on slope of the Khibiny Mountains, the Altai, the Baikal Mountains, and the Caucasus are presented in the article. Monitoring of the snow cover stability on slopes and the avalanche forecasting are the most difficult actions to be carried out in areas with great spatial variability of snow. The Khibiny Mountains are first of all such area among other ones.